Validation of the Danish Version of Functional Assessment of Multiple Sclerosis: A Quality of Life Instrument. (19th December 2011) - Sørensen, Jan; Bay, Jette; Damsgaard, Torben; Heeley, Elsebeth; Rostgaard, Ida; Løvendahl, Brita; Boesen, Finn
Abstract : The functional assessment of multiple sclerosis (FAMS) is a disease-specific instrument that describes functional status of individuals with multiple sclerosis. The instrument was originally developed in the US and has been adapted to different languages including Danish. This study is a validation of the Danish version of FAMS in a sample of individuals referred to a four-week rehabilitation program at either of the two Multiple Sclerosis Rehabilitation centers in Denmark. FAMS data were obtained through self-completed questionnaires from 190 individuals who attended the rehabilitation centers after referral by their general practitioner or specialist neurologist. The validation of the FAMS included assessment of data quality, scale assumptions, acceptability, construct validity, and reliability. Responsiveness was assessed by comparing individual FAMS scores at admission with the discharge score for groups of respondents who reported no change, improvement, or deterioration in their ability to cope with their illness. The Danish version of FAMS appears to be an acceptable, valid, and reliable measure of current health and functional status of individuals with multiple sclerosis.